PHONETICS AND PHONOLOGY OF THE RUSSIAN LANGUAGE - Sultanmurodova Farangis Akramovna; Erkinova Parvina Akramovna; Boltayeva Farida Oybekovna (European Science Publishing, 2024)
The article is devoted to the study of phonetics and phonology of the Russian language. It examines the main sounds of the Russian language, the features of pronunciation of vowels and consonants, as well as such important phonological phenomena as stress, softening of consonants, assimilation and reduction. The differences between hard and soft consonants, their role in changing the meaning of words, as well as the processes of devoicing and simplification of sounds in words are described. Knowledge of these features is necessary for correct pronunciation and a deep understanding of the structure of the Russian language.
Keywords: Phonetics of the Russian language, phonology of the Russian language, vowel reduction, softening of consonants, phonetic stress, assimilation of sounds, palatalization, hard and soft consonants, consonant clusters, sound system of the Russian language.